Expansion of ability of denitrification within the filamentous colorless sulfur bacteria of the genus Thiothrix. Issue 1 (1st September 2014) - Trubitsyn, Ivan V.; Belousova, Elena V.; Tutukina, Maria N.; Merkel, Alexander Y.; Dubinina, Galina A.; Grabovich, Margarita Y.
Abstract: Filamentous sulfur bacteria of the genus Thiothrix are able to respire nitrate ( ) under anaerobic growth. Here, Thiothrix caldifontis (G1 T, G3), Thiothrix unzii (A1 T, TN) and Thiothrix lacustris AS were shown to be capable of further reduction of nitrite and/or nitrous oxides (denitrification). In particular, in the genomes of these strains, excluding T. unzii TN, the nirS gene encoding periplasmic respiratory nitrite reductase was detected, and for T. lacustris AS the nirS expression was confirmed during anaerobic growth. The nirK gene, coding for an alternative nitrite reductase, and the nrfA gene, encoding nitrite reduction to ammonia, were not found in any investigated strains. All Thiothrix species capable of denitrification possess the cnorB gene encoding cytochrome c-dependent NO reductase but not the qnorB gene coding for quinol-dependent NO reductase. Denitrifying capacity ('full' or 'truncated') can vary between strains belonging to the same species and correlates with physical-chemical parameters of the environment such as nitrate, hydrogen sulfide and oxygen concentrations. Phylogenetic analysis revealed the absence of recent horizontal transfer events for narG and nirS ; however, cnorB was subjected to gene transfer before the separation of modern species from a last common ancestor of the Thiothrix species. Abstract : Representatives of the T hiothrix genus are capable of denitrification as an adaptive mechanism under stress conditions. Abstract :